Surgical treatment of isolated right ventricular metastasis from renal cell carcinoma - Shuhei Miura; Akira Yamada; Yutaka Iba; Ryushi Maruyama; Eiichiro Hatta; Yoshihiko Kurimoto (Surgical Case Reports)
Abstract Background Cardiac metastasis from renal cell carcinoma is an exceptional event, particularly when there is lack of inferior vena cava involvement. Only a few cases have been reported worldwide so far. Case presentation We presented a case of a 58-year-old man diagnosed with isolated right ventricular metastasis of renal cell carcinoma in the absence of direct inferior vena cava extension, who underwent surgical tumor resection using cardiopulmonary bypass. Conclusions Surgical resection of the cardiac mass with an understanding of the pathology is needed to prevent sudden death from acute heart failure or tumor embolism and improve the patient’s quality of life.